2016
DOI: 10.1111/jpn.12436
|View full text |Cite
|
Sign up to set email alerts
|

Energy utilization, nitrogen balance and microbial protein supply in cattle fed Pennisetum purpureum and condensed tannins

Abstract: The aim of the experiment was to assess the effect of condensed tannins (CT) on feed intake, dry matter digestibility, nitrogen balance, supply of microbial protein to the small intestine and energy utilization in cattle fed a basal ration of Pennisetum purpureum grass. Five heifers (Bos taurus × Bos indicus) with an average live weight of 295 ± 19 kg were allotted to five treatments consisting of increasing levels of CT (0, 1, 2, 3 and 4% CT/kg DM) in a 5 × 5 Latin square design. Dry matter intake (DMI) was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 53 publications
0
3
0
4
Order By: Relevance
“…Recently, Piñeiro‐Vázquez et al. () observed that only doses of 40 g/kg DM of condensed tannins reduced feed intake in heifers. Thus, the condensed tannins found in PLP diets might be too low to have negative effects on feed intake and consequently on growth performance.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Piñeiro‐Vázquez et al. () observed that only doses of 40 g/kg DM of condensed tannins reduced feed intake in heifers. Thus, the condensed tannins found in PLP diets might be too low to have negative effects on feed intake and consequently on growth performance.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Stević et al ( 2010 ) demonstrated that A. viridis leaves can have a tannin concentration of 44 ± 4 g kg −1 DM, which can form tannin-protein complexes by binding with plant proteins when consumed by livestock (Harris et al 1998 ; Waghorn 2008 ; Woodfield et al 2019 ). These complexes are better protected from rumen microbial degradation and they can thus reduce the degradation of N during digestion (Waghorn et al 1987 ; Burggraaf and Snow 2010 ; Piñeiro-Vázquez et al 2017 ). Therefore, the passage of undegraded N could be favored through the intestine and through dung, and a smaller proportion of N might be excreted in urine (Burggraaf and Snow 2010 ; Theodoridou et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, los TC presentes en Havardia albicans, Acacia pennatula y Bursera simaruba incorporados al 30% en la dieta, no afectaron la metanogénesis. Sin embargo, concentraciones de TC de entre 2 y 3% de la MS en la alimentación de novillas resultó en una reducción del 31% y 47 % de la pérdida de energía en forma de metano, sin afectar el consumo de MS y MO, aunque su digestibilidad se vio comprometida (Piñeiro-Vázquez et al, 2017).…”
Section: Taninosunclassified